AKTUALISASI PEMAHAMAN NILAI MENURUT MAX SCHELER BAGI MASA DEPAN BANGSA INDONESIA - Jirzanah, Jirzanah (Jurnal Filsafat "WISDOM", 2008)
AbstractScheler is a philosopher who argues that philosophy and real life are not inseparable. Scheler does not base his ideas in aspecific scientific procedure and have no an empirical procedure, but uses an intuition to perform a direct relation with the reality. A morality of human being relied into effect of objective values. A value arrested directly pursuant to intuition. The targets of this research are to formulate descriptively a background philosophical theory of Scheler axiology, values essence, and base of an understanding of values, later then formulate analytically an excess and weakness of Scheler axiology, and basic axiology to Indonesian nation in the future.This research is a library research in Philosophy. Source ofdata collected from bibliographic books which related with thematerial object of this research. The material object of this research is theory Scheler about value. The formal object of this research is Axiology. A primarily materials of this research are books have published about Scheler masterpiece in Ethics and value theory. The steps of this research are sort in data collecting, reduce the data, data classification, interpretation, recapitulating, and reporting. Method of data analyze uses the understanding of interpretation and hermeneutic.The result of this research showed that idea of Scheler philosophy is influenced by Husserl phenomenology. Phenomenology represented methods and philosophy. Phenomenology as a method sorts the steps which must be taken to be able to pure phenomenon. Someone have to starting from subject and its awareness and also to return a pure awareness (intuition). Scheler have a notion, that value look of human being because sticked at a reality. Intelligence or mind cannot have a kind of direct link with values. Values express human being through the emotional intuition (consciousness). The principles of axiology are needed in the nation and state guidance so that pluralism can become the nation strength. An understanding of values through life sensitivity is important in answering multiculturalism of Indonesia. The principles of humanity, unity, and contextuality can be accepted with the sensitivity. The principles of unity and contextuality can make an ethnical group comprehend and have empathy to the other ethnical group values. If multiculturalism is understood through the rational approach, it will emerge ‘right and wrong’ justification without consideration of tolerance and empathy.Keywords: philosophy, values, Indonesian, real life.